ENTRE IDÉAL, ÉTHIQUE ET LOI: L’ÉQUITÉ - Jean-Jacques SARFATI (Studia Universitatis Babeș-Bolyai. Philosophia)
Equity between Ideal, Ethics and Law. The purpose of this text is to show that equity is now a need for our post-modernity. However, it can only become a reality only if it is applied by an elite that regains the support of the people and of the intellectual sphere. Without this support and reality, the legal philosophy seeks to build it without being able to convince completely. Indeed, equity cannot be only an idea - it must be a concrete reality and at work. Otherwise, it vanishes.